O direito à moradia e o direito à cidade na política de regularização fundiária urbana de interesse social. As experiências de REURB-S nas comunidades África e Passo da Pátria, em Natal/RN - Dias, Fernanda Maria da Mata (2023)
The right to housing and the right to the city are basic human rights, essential for guaranteeing human dignity, and which are part of the existential minimum. Decent housing and access to a sustainable city, however, are still objectives to be achieved by the Brazilian State, a country marked by social chasms, which have historical roots and which were aggravated by the unbridled urbanization process that devastated the country from the mid-19th century onwards. of the last century. As a result of the uneven urbanization process, slums, tenements, spaces of poverty, and self-construction of housing emerged. A possible path to the issue of urban informality and urban exclusion is urban land regularization, a policy that aims to improve the quality of urban life of the population, with the implementation of public services, infrastructure and land legalization. This, however, is only one point of view about this policy, which isconceived by some theorists and public agents only under the aspect of land legalization.In the period between 2001 and 2016, a conception of land and urban regularization prevailed in Brazil based on the association between urban improvement projects, registrytitling and housing improvements, the so-called “Brazilian Formula”. However, the newBrazilian political directions gave rise to the publication of Federal Law No. 13,465-2017,which changed the paradigm of land regularization in Brazil, which ceased to privilege environmental, social and urbanistic aspects, moving to a model focused on registry titling. It is in the face of this problem, which gives rise to studies on the effects of Law nº 13.465/2017 in concrete cases, that the present research seeks to understand the consequences of the implementation of the land regularization policy in the municipalityof Natal/RN, in view of the changes promoted by the Law nº 13.465/2017 and in the lightof the rights to housing and the city, using as a parameter the cases of the communities África and Passo da Pátria, between 2015 and 2023. In the methodological aspect, a comparative study was used, seeking approximations and differences between the REURB-S processes in Africa and Passo da Pátria, in Natal/RN. Research techniques include a bibliographic survey, document analysis, direct observations and interviews with public agents and residents of the studied communities. The results obtained allow the conclusion that the premise was confirmed, when verifying, in two practical cases, the deficient protection of the rights to housing and to the city, in the land regularizationpolicy in the municipality of Natal/RN, with the Reurb-S from Africa and Passo da Pátriawere carried out solely with a focus on the registration title